2020
DOI: 10.2147/clep.s230537
|View full text |Cite
|
Sign up to set email alerts
|

<p>Associations Between Psychiatric Disorders and Enuresis in Taiwanese Children: A National Population-Based Study</p>

Abstract: Background: Psychiatric disorders such as attention-deficit/hyperactivity disorder may negatively impact drug compliance and the prognosis of enuresis. However, existing studies regarding associations between lifetime psychiatric disorders and childhood enuresis are primarily from Western countries, and studies from Taiwan are lacking. Methods: We conducted a population-based retrospective cohort analysis using the Taiwan Longitudinal Health Insurance Database 2010. A total of 1,146 children with enuresis (ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the rate was similar to that of studies in tertiary care sample with ADHD being the most common psychiatric disorder among enuretic children. 4,17 This study also revealed higher rate of significant externalizing problems which included symptoms of ADHD. Although several participants from our child psychiatric clinic might have a diagnosis of ADHD and its treatment 18 , we did not collect any of the psychiatric diagnosis in our sample.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…However, the rate was similar to that of studies in tertiary care sample with ADHD being the most common psychiatric disorder among enuretic children. 4,17 This study also revealed higher rate of significant externalizing problems which included symptoms of ADHD. Although several participants from our child psychiatric clinic might have a diagnosis of ADHD and its treatment 18 , we did not collect any of the psychiatric diagnosis in our sample.…”
Section: Discussionmentioning
confidence: 59%
“…Other studies also demonstrated higher prevalence in younger children and decreasing rates with increasing age. 4 Association between LUTs i.e., detrusor overactivity in NMNE and constipation is also common. 11,13 There was an extremely high rate of the clinical range of the TYC in the study population (78.8%) compared to those of other studies of children with enuresis (20-40%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations